2020
DOI: 10.3389/fpsyt.2020.599945
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Clinical Efficacy Through the Lens of Audit Data in Different Adult Eating Disorder Treatment Programmes

Abstract: Background: Audit data is important in creating a clear picture of clinical reality in clinical services, and evaluating treatment outcomes. This paper explored the data from an audit of a large national eating disorder (ED) service and evaluated the outcome of inpatient and day treatment programmes for patients with anorexia nervosa (AN) with and without autistic traits.Methods: Four hundred and seventy-six patients receiving treatment for AN at inpatient (IP), day-care (DC) and step-up (SU) programmes were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 48 publications
5
13
0
Order By: Relevance
“…The present findings lend further credence to previous work documenting that people with AN who report high levels of autistic traits have more severe psychological presentation (Li et al, 2020;Stewart et al, 2017;Tchanturia et al, 2019). Furthermore, the present findings add to the literature by highlighting that high levels of autistic traits predict poorer psychological outcome in long term.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The present findings lend further credence to previous work documenting that people with AN who report high levels of autistic traits have more severe psychological presentation (Li et al, 2020;Stewart et al, 2017;Tchanturia et al, 2019). Furthermore, the present findings add to the literature by highlighting that high levels of autistic traits predict poorer psychological outcome in long term.…”
Section: Resultssupporting
confidence: 88%
“…Similarly previous studies have documented that autistic traits not associated with BMI, but were strongly associated with psychological symptoms and general level of social functioning, among people with lived experience of AN (Kerr-Gaffney et al, 2020;Tchanturia et al, 2019). A recent examination of clinical audit data showed that AN patients reporting high levels of autistic traits had significantly higher BMI upon admission to inpatient care (Li et al, 2020). The focus on BMI as the measure of recovery, in particular, has been highlighted as less helpful for autistic people with AN, who discuss the psychological elements of recovery as being more difficult for them to manage (Sedgewick et al, 2021).…”
Section: Resultsmentioning
confidence: 56%
“…The present ndings lend further credence to previous work documenting that people with AN who report high levels of autistic traits have more severe psychological presentation (24,25,39). Furthermore, the present ndings add to the literature by highlighting that high levels of autistic traits predict poorer psychological outcome in long term.…”
Section: Discussionsupporting
confidence: 87%
“…Kinnaird and colleagues demonstrated that patients with EDs, with and without autism spectrum comorbidity, are hypersensitive to smells, touch and noise, and hypersensitivity in different domains could be addressed in their treatment [ 4 – 6 ]. Clinical audit data shows that almost 37% of people with AN treated in inpatient and day-care programmes have high Autism Spectrum Condition (ASC) traits and are therefore likely to experience some sensory differences [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the novel clinical pathway for autism and eating disorders, PEACE (Pathway for Eating disorders and Autism developed from Clinical Experience), we have started to measure sensory sensitivities in patients and have developed psychoeducation materials and experiential activities to support sensory wellbeing [ 8 ]. We also found that patients with no autistic traits as well as high autistic traits benefited from the sensory changes made in the dining room evidenced with focus groups [ 9 ]. Based on the research evidence [ 4 , 10 ], we have developed one-off workshops which offer both psychoeducational content and experiential activities to support patients by creating a soothing and helpful sensory toolkit.…”
Section: Introductionmentioning
confidence: 99%